Courses
Courses for Kids
Free study material
Offline Centres
More
Store Icon
Store

If $ x={{\sin }^{-1}}(\sin 10) $ and $ y={{\cos }^{-1}}(\cos 10) $ , then y – x is equals to

seo-qna
Last updated date: 17th Jun 2024
Total views: 412.2k
Views today: 11.12k
Answer
VerifiedVerified
412.2k+ views
Hint: To solve this question we will take the help of graph of functions $ y={{\sin }^{-1}}(\operatorname{sinx}) $ and $ y={{\cos }^{-1}}(cosx) $ . What we will do is we will check on which line the value 10 on graph $ y={{\sin }^{-1}}(\operatorname{sinx}) $ and $ y={{\cos }^{-1}}(cosx) $ as graphs of functions $ y={{\sin }^{-1}}(\operatorname{sinx}) $ and $ y={{\cos }^{-1}}(cosx) $ are continuous.
Then, finally we will evaluate the value of y and x and hence find y – x .

Complete step-by-step answer:
Before we solve the question to get value of y – x ,
Let us see the properties and graph of function $ y={{\sin }^{-1}}(\operatorname{sinx}) $ .
 $ {{\sin }^{-1}}(\operatorname{sinx})=-\pi -x;\dfrac{-3\pi }{2}\le x\le \dfrac{-\pi }{2} $ ,
        $ =x;\dfrac{-\pi }{2}\le x\le \dfrac{\pi }{2} $ ,
        $ =\pi ;\dfrac{\pi }{2}\le x\le \dfrac{3\pi }{2} $ .
And, graph of $ y={{\sin }^{-1}}(\operatorname{sinx}) $ is given as ,
seo images

Let us see the properties and graph of the function $ y={{\cos }^{-1}}(cosx) $ .
 $ {{\cos }^{-1}}(cosx)=-x;-\pi \le x\le 0 $
         $ =x;0\le x\le \pi $
         $ =2\pi -x;\pi \le x\le 2\pi $
And, graph of $ y={{\cos }^{-1}}(cosx) $ is given as ,
seo images

Now, let us solve for $ x={{\sin }^{-1}}(\sin 10) $ first,
As we see that, $ \dfrac{5\pi }{2}\le 10\le \dfrac{7\pi }{2} $
So, we can say that 10 lies on line $ 3\pi -x $ , so 10 will satisfy the equation $ y=3\pi -x $
Putting x = 10 in $ y=3\pi -x $ , we get
 $ y=3\pi -10 $ .
Or, $ 3\pi -10={{\sin }^{-1}}(\sin 10) $ …… ( i )
Now, let us solve for $ y={{\cos }^{-1}}(cos10) $ ,
As we see that, $ 3\pi \le 10\le 4\pi $ ,
So, we can say that 10 lies on line $ 4\pi -x $ , so 10 will satisfy the equation $ y=4\pi -x $
Putting x = 10 in $ y=4\pi -x $ , we get
 $ y=4\pi -10 $ .
Or, $ 4\pi -10={{\cos }^{-1}}(cos10) $ …..( ii )
Now, we have to find the value of, y – x that is $ {{\cos }^{-1}}(cos10)-{{\sin }^{-1}}(\sin 10) $ ,which is equals to
 $ y-x=(4\pi -10)-(3\pi -10) $ .

Note: Graph of $ y={{\sin }^{-1}}(\operatorname{sinx}) $ and $ y={{\cos }^{-1}}(cosx) $ are very important function and graphs should be remembered while solving questions based on inverse trigonometric functions. The value of input should be checked on which line of the function does it lie carefully as it may change the output of the function.